2021
DOI: 10.1002/rmv.2295
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and secondary infection risk of tocilizumab, sarilumab and anakinra in COVID‐19 patients: A systematic review and meta‐analysis

Abstract: Summary As the pandemic progresses, the pathophysiology of coronavirus disease 2019 (COVID‐19) is becoming clearer and the potential for immunotherapy is increasing. However, clinical efficacy and safety of immunosuppressants (including tocilizumab, sarilumab and anakinra) treatment in COVID‐19 patients are not yet known. We searched PubMed, Embase Medline, Web of Science and MedRxiv using specific search terms in studies published from 1 January 2020 to 20 December 2020. In total, 33 studies, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 29 publications
2
27
0
4
Order By: Relevance
“…Studies have shown that anakinra treatment can significantly reduce mortality in COVID-19 patients without increasing the risk of infection and with no side effects. Anakinra is therefore an ideal broad-spectrum therapeutic drug [ 123 , 124 ]. In a recent study, 10 hospitalized adults with bilateral pneumonia, excessive inflammation, and respiratory failure who did not require mechanical ventilation showed a rapid decrease in serum CRP, improved oxygenation, and no granulocytopenia or bacterial septicemia during 45 days of hospitalization when treated with canakinumab [ 125 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Studies have shown that anakinra treatment can significantly reduce mortality in COVID-19 patients without increasing the risk of infection and with no side effects. Anakinra is therefore an ideal broad-spectrum therapeutic drug [ 123 , 124 ]. In a recent study, 10 hospitalized adults with bilateral pneumonia, excessive inflammation, and respiratory failure who did not require mechanical ventilation showed a rapid decrease in serum CRP, improved oxygenation, and no granulocytopenia or bacterial septicemia during 45 days of hospitalization when treated with canakinumab [ 125 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, despite poor evidence regarding the matter, a significant number of patients is treated with empiric broad-spectrum antibiotic therapy, thus increasing the risk of developing infections caused by multidrug-resistant (MDR) pathogens [ 7 ]. Lastly, the use of drugs targeting cytokines such as IL-6 in patients with the so-called COVID-19-related “cytokine storm” also may constitute a risk factor for superinfection by compromising the immune system [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Others have raised similar concerns. 4 A meta-analysis by Peng et al identified an increased risk of fungal infections (odds ratio, 2.02), 10 and a large retrospective study is underway to further describe infection risks associated with tocilizumab (https:// clinicaltrials.gov/ct2/show/NCT05017441).…”
Section: Discussionmentioning
confidence: 99%